The Effect of Entrepreneurial Leadership on Innovation Performance in SMEs: A Systematic Literature Review - Sai, Cui; Omar, Ahmad Raflis Che; Hizam-Hanafiah, Mohd; Juhdi, Noor Hasni (Journal of Ecohumanism, 2024)
Innovation performance (IP) is currently crucial for small and medium-sized enterprises (SMEs). Entrepreneurial leadership (EL) ensures competitive advantages and sustainability in the contemporary global landscape. Previous studies have observed and evaluated this field’s trends and focal points. The purpose of this study is to conduct a systematic literature review of previous studies on the effect of EL on IP in SMEs. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement was used to evaluate the systematic literature in the study. Articles from the years 2000 to 2023 were searched in the Scopus and Web of Science databases (WoS). Fourteen articles were included in the final process. There have been limited studies undertaken on this topic in recent decades, and fresh findings are involved with this topic after 2012. As a new paradigm to enhance innovation and sustainability, EL has become increasingly crucial in SMEs. The present study utilizes the PRISMA approach to summarize the effect of EL on IP in SMEs, acting as one reference point for ongoing research. The study also discusses the limitations and provides recommendations for subsequent analysis.